Forerunners vs. latecomers: Institutional competition in the German federalism during the COVID crisis - Lukas Breide; Oliver Budzinski; Thomas Grebel; Juliane Mendelsohn (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2023)
The COVID pandemic caused the political competition between the prime ministers of the German states to reach its peak. Whoever is the best at announcing, launching, or implementing policies to combat the pandemic can hope to capitalize most politically. In this paper, we attempt to document which state leaders are forerunners or latecomers in this political competition, when going more into depth of a region's contextual factors. Based on several databases, we perform a survival analysis to compare state leaders' relative determination to implement COVID policies. As our results show, the forerunners in the political discourse are not necessarily forerunners in the implementation, nor in the enforcement of COVID policies.
Keywords: D7; H7; H11; H12; R5; 330; Corona; COVID; political competition; institutions; survival analysis